If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 = 28x + 36 Reorder the terms: 85 = 36 + 28x Solving 85 = 36 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 85 + -28x = 36 + 28x + -28x Combine like terms: 28x + -28x = 0 85 + -28x = 36 + 0 85 + -28x = 36 Add '-85' to each side of the equation. 85 + -85 + -28x = 36 + -85 Combine like terms: 85 + -85 = 0 0 + -28x = 36 + -85 -28x = 36 + -85 Combine like terms: 36 + -85 = -49 -28x = -49 Divide each side by '-28'. x = 1.75 Simplifying x = 1.75
| -3w-2z=-8 | | -6+8=122 | | 20=-4.9t^2+40t | | 12x+12-(x-1)=12 | | -(y+6)+2y-4=-19 | | 8+z=42 | | 6x+y+9=9x | | 6=-2x+6 | | .38x=34 | | 3(x+4)=-2(5x-8)+7x | | 4x+18=2(x+6) | | -2(4z-3)+9(z-6)=-32-8 | | 6x+7=(m) | | -20x-(-15x)=-165 | | 11-3(2x+4y)= | | 3x+2=10x-26 | | -8+14=-2(4v-7) | | 5.3+z=-9 | | 25.61+4.1= | | 3(w-3)=w+4-5(-2w-1) | | -2(3Z-5)+7(z-7)=-13-6 | | 9x^4-66x^2+121=0 | | 25r-25r+25r=5-2.5r | | n+6=96 | | -(y+15)+2y-12=-27 | | x^4-x^2=47x^2+49 | | -3(3u-1)+5u=9+4(2u-4) | | (7r^3-6r-6)(2r-4)= | | 62(x+20)=90 | | -(y+15)+2y-12=-42 | | t^3-10t+21=0 | | 9(s+6)-8s=45 |